Work time. Leisure time. On women’s temporal and economic wellbeing in Europe - Warren, Tracey (Taylor and Francis, 2010)
In the study of work time, a wealth of influential ideas have emerged about the potentially damaging impact of too many hours in the labour market on the rest of peoples’ lives, as well as about the negative economic ramifications of short hours working. The paper focuses on the temporal and economic wellbeing of female employees in Europe, stimulated by the importance of work time in debates over time poverty and work life integration. It asks whether women in shorter hours jobs are happiest with their time, for paid work and leisure, but also what might the lower wages from reduced hours working mean for women, particularly those in low level occupations. The paper shows first that although working fewer hours contributes to women’s satisfaction with their time in many countries, it is long full-time hours that have the strongest (negative) relationship with women’s temporal wellbeing across Europe. Second, the paper demonstrates the damaging impact of working in low level occupations – both part-time and full-time - on the economic wellbeing of women’s households. It stresses the importance of a combined work time and occupational class approach in the ongoing analysis of women’s working lives.